1991
DOI: 10.1002/ppul.1950100403
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lung mechanics and histamine responsiveness after sequential canine adenovirus 2 and canine parainfluenza 2 virus infection in beagle puppies

Abstract: We determined the effects of an immediately antecedent viral lower respiratory tract infection (LRI) on the severity of clinical illness, changes in lung function and airway histamine responsiveness produced by a subsequent LRI in 9-12 week old beagle puppies inoculated with canine adenovirus 2, followed in 2 weeks by inoculation with canine parainfluenza 2 virus (CAV2-CP12, n = 7). We compared their acute responses to puppies infected with CP12 alone (n = 5), CAV2 alone (n = 7), and no infection (control, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As originally observed in early studies of CITB outbreaks and later confirmed prospectively, [51][52][53][54] CPIV infection results in more severe respiratory disease when complicated by coinfection with other viruses and bacteria. This pathological synergism in CITB is similar to PIV infections in other species, notably BPIV type 3 infection and shipping fever in cattle.…”
Section: Pathogenesis Of Cpiv Infectionmentioning
confidence: 68%
See 3 more Smart Citations
“…As originally observed in early studies of CITB outbreaks and later confirmed prospectively, [51][52][53][54] CPIV infection results in more severe respiratory disease when complicated by coinfection with other viruses and bacteria. This pathological synergism in CITB is similar to PIV infections in other species, notably BPIV type 3 infection and shipping fever in cattle.…”
Section: Pathogenesis Of Cpiv Infectionmentioning
confidence: 68%
“…In human medicine, an area of investigation in the pathogenesis of pediatric PIV infections has been the potential role of these viruses as a risk factor for the development of airway hyperreactivity and chronic airway obstruction later in life. 17 A considerable part of this research has actually been done with CPIV infection in dogs 22,[49][50][51][52][53] and has fortuitously provided greater insights into CPIV-associated pathophysiologic changes in dogs. Experimentally, infection of 2-to 3-monthold laboratory Beagles with CPIV consistently resulted in transient airway hyperresponsiveness to aerosolized histimine.…”
Section: Pathogenesis Of Cpiv Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary function. We measured pulmonary function by methods developed and routinely used in our laboratory (20,22,23). Briefly, airflow was measured with a heated pneumotachograph (Fleisch no.…”
Section: Methodsmentioning
confidence: 99%